PEMAHAMAN SANTRI PONDOK PESANTREN AZZAKARIYAH, RENAH, MERANGIN, TERHADAP HADIS-HADIS MISOGINIS (Thobaqot: Jurnal Ilmu Hadis, 2023)
This article discusses the understanding of the students of the Merangin Azzakariyah Islamic Boarding School regarding misogynistic hadiths. The problems raised in this paper are: (1) How do the students of the Azzakariyah Islamic Boarding School understand misogynist hadiths? (2) What is the impact of misogynist hadith on the lives of students at the Azzakariyah Islamic Boarding School? This paper uses qualitative methods. Data was collected through participant observation. The data was then analyzed through several stages, namely data reduction, data presentation, and drawing conclusions. Testing the validity of the data through diligent observation, triangulation and peer discussion. The results of this paper found that: (1) students' understanding of misogynist hadiths varies, some understand it textually and some understand it contextually; and (2) the impact of misogynistic hadiths on the lives of the students of the Azzakariyah Islamic Boarding School is the existence of textual understanding for female students in understanding misogynist hadiths, so that the activities of the students are the legitimization of social institutions which ultimately reach a generality called a worldview.